2019
DOI: 10.1159/000503323
|View full text |Cite
|
Sign up to set email alerts
|

Overdiagnosis of Juvenile Thyroid Cancer

Abstract: Overdiagnosis is the detection of a disease that does not do any harm to the patient throughout the lifetime. Thyroid cancer in children is a rare disease; however, since 2011, many children in Fukushima, Japan, have been diagnosed with it, and the number has shown a steady increase to over 200 cases at present. Some experts have stated that this phenomenon is due to overdiagnosis caused by thyroid ultrasound (US)-based thyroid screening detecting self-limiting thyroid cancer, which will not lead to clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Thyroid examination is the cause of anxiety in Fukushima. 2 The need for psychological care during the secondary confirmatory examination described in this letter confirms that the examination is traumatic for the children and their parents. Furthermore, introduction of population-based thyroid screening for anxiety relief cannot be ethically justified because those who are worried are usually the parents, not their children who are under the threat of overdiagnosis.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…Thyroid examination is the cause of anxiety in Fukushima. 2 The need for psychological care during the secondary confirmatory examination described in this letter confirms that the examination is traumatic for the children and their parents. Furthermore, introduction of population-based thyroid screening for anxiety relief cannot be ethically justified because those who are worried are usually the parents, not their children who are under the threat of overdiagnosis.…”
supporting
confidence: 60%
“…Although thyroid radiation doses in Fukushima were thought to be relatively low, individual organ-specific measurements were rare, so a degree of uncertainty remains. A recent report 2 suggests the possibility of radiation-induced risks in pediatric thyroid carcinoma in Fukushima. Accordingly, most Japanese scientists and local stakeholders feel that health effects associated with radionuclides released by our nuclear plant accident have not been scientifically excluded, and that at least 10 years will be needed to determine whether increased risk of pediatric thyroid cancer is present.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Considering these results together, most papillary thyroid cancers are characterized by self-limiting growth in a growth arrest pattern, forming a large pool of latent cancer as a reservoir that cannot be detected without screening ( Fig. 1 ) [ 10 , 15 , 33 , 34 ]. It is thought that most papillary thyroid cancers show a self-limiting course like type â‘  in the figure.…”
Section: Thyroid Examinations In the Fukushima Health Management Surveymentioning
confidence: 99%
“…Our research team previously reported an increasing trend of childhood thyroid cancer in Korea until 2012 and since most children are not screened for thyroid cancer, 72% of childhood thyroid cancers were detected by palpation rather than screening (14). However, some experts stated that the increased incidence of childhood thyroid cancer is due to overdiagnosis by US-based screening (15).…”
Section: Introductionmentioning
confidence: 99%